Effectiveness of indoor allergen reduction in asthma management: A systematic review - Leas, Brian F.; D'Anci, Kristen E.; Apter, Andrea J.; Bryant-Stephens, Tyra; Lynch, Marcus P.; Kaczmarek, Janice L.; Umscheid, Craig A. (Journal of allergy and clinical immunology, 2018)
This review will inform updated National Asthma Education and Prevention Program clinical practice guidelines. We sought to evaluate the effectiveness of allergen reduction interventions on asthma outcomes. We systematically searched the “gray literature” and 5 bibliographic databases. Eligible studies included systematic reviews, randomized controlled trials, and nonrandomized interventional studies. Risk of bias was assessed by using the Cochrane Risk of Bias instrument and the Newcastle-Ottawa scale. The evidence base was assessed by using the approach of the Agency for Healthcare Research and Quality's Evidence–based Practice Center program. Fifty-nine randomized and 8 nonrandomized trials addressed 8 interventions: acaricide, air purification, carpet removal, high-efficiency particulate air filtration (HEPA) vacuums, mattress covers, mold removal, pest control, and pet removal. Thirty-seven studies evaluated single-component interventions, and 30 studies assessed multicomponent interventions. Heterogeneity precluded meta-analysis. For most interventions and outcomes, the evidence base was inconclusive or showed no effect. No interventions were associated with improvement in validated asthma control measures or pulmonary physiology. Exacerbations were diminished in multicomponent studies that included HEPA vacuums or pest control (moderate strength of evidence [SOE] for both). Quality of life improved in studies of air purifiers (SOE: low) and in multicomponent studies that included HEPA vacuums (SOE: moderate) or pest control (SOE: low). Single interventions were generally not associated with improvement in asthma measures, with most strategies showing inconclusive results or no effect. Multicomponent interventions improved various outcomes, but no combination of specific interventions appears to be more effective. The evidence was often inconclusive because of a lack of studies. Further research is needed comparing the effect of indoor allergen reduction interventions on validated asthma measures, with sufficient population sizes to detect clinically meaningful differences. [Display omitted]